2021
DOI: 10.1098/rspb.2021.0281
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic diversification of Eranthis (Ranunculaceae) reflects the geological history of the three great Asian plateaus

Abstract: The evolutionary history of organisms with poor dispersal abilities usually parallels geological events. Collisions of the Indian and Arabian plates with Eurasia greatly changed Asian topography and affected regional and global climates as well as biotic evolution. However, the geological evolution of Asia related to these two collisions remains debated. Here, we used Eranthis , an angiosperm genus with poor seed dispersal ability and a discontinuous distribution across Eurasia, to shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Since there are different definitions of the term "basic chromosome number (x)" concerning polyploids (Peruzzi 2013), we clarify that, in the study, we mean, "x" as "chromosome number found in the gametes of their diploid relatives", according to Darlington (1958). A recent phylogenetic study (Xiang et al 2021) found that E. tanhoensis and E. sibirica are closely related species that formed separate groups with basic chromosome number x = 7 within the North Asian clade of Eranthis. The same basic chromosome number x = 7 with 2n = 14 was previously reported in the genus Eranthis for E. stellata (Starodubtsev 1985), albeit this author does not provide any microphotograph of the metaphase plate.…”
Section: Karyotype Structure In Eranthismentioning
confidence: 99%
See 2 more Smart Citations
“…Since there are different definitions of the term "basic chromosome number (x)" concerning polyploids (Peruzzi 2013), we clarify that, in the study, we mean, "x" as "chromosome number found in the gametes of their diploid relatives", according to Darlington (1958). A recent phylogenetic study (Xiang et al 2021) found that E. tanhoensis and E. sibirica are closely related species that formed separate groups with basic chromosome number x = 7 within the North Asian clade of Eranthis. The same basic chromosome number x = 7 with 2n = 14 was previously reported in the genus Eranthis for E. stellata (Starodubtsev 1985), albeit this author does not provide any microphotograph of the metaphase plate.…”
Section: Karyotype Structure In Eranthismentioning
confidence: 99%
“…This hypothesis is because most of the tribe Cimicifugeae members (i.e., Actaea, Anemonopsis, Beesia, Cimicifuga, Souliea and closely related Helleborus; Wang et al 2009) have x = 8 (Rice et al 2015). In addition, it has been established that Eranthis originated in East Asia and then dispersed to the west Qinghai-Tibetan Plateau and Mediterranean regions (Xiang et al 2021). East Asian Eranthis species (i.e., E. byunsanensis, E. lobulata, E. pinnatifida, and E. stellata) have x = 8.…”
Section: Karyotype Structure In Eranthismentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Eranthis Salisb. belongs to the tribe Cimicifugeae of the family Ranunculaceae Juss., with 13 species occurring on a territory covering a part of Europe and Asia [1,2]. Representatives of this genus are perennial herbs with tuberous rhizomes or tubers and basal long petiolate leaves with the blades divided into several or many palmate segments that are undivided or lobate; unbranched scapes carry a solitary bisexual actinomorphic flower supported by three verticillate leaf-like bracts forming involucrate leaves; there are (4-)5-8 yellow, white or pink, petaloid sepals as well as 5-10(-15) yellow or white, petaloid, or slightly concave tubular petals, shorter than sepals, sometimes with pseudonectaries; nectaries are located inside the tubular petal; there are >10 stamens and 3-10 follicles with several smooth seeds in each fruitlet [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Shibateranthis have tubers, white sepals, and a bilobate or forked petal apex, sometimes with pseudonectaries [6]. Phylogenetic studies support the subdivision of the genus into these sections [2,7].…”
Section: Introductionmentioning
confidence: 99%